„Jesteśmy żywą materią i żywa materia nas otacza, choć nie zawsze to dostrzegamy”. Kategoria życia w nowym materializmie - Kowalcze, Małgorzata (Załącznik Kulturoznawczy, 2022)
The paper discusses selected elements of the New Materialist reformulation of the notion of life. It focuses on two theories existing within the new materialist framework, i.e. Jane Bennett’s vital materialism as well as Rosi Braidotti’s zoecentrism. Braidotti distinguishes between bios – biological life of individual creatures, characterized by species-specific qualities, and zoe – unspecified life force in which all the living creatures partake. According to her, the notion of life does not exhaust itself in exercising certain biological functions nor is the human life by definition a more developed form of life. Braidotti emphasizes the primacy and unifying function of zoe, arguing that the lives of non-human beings should be given more attention and appreciation. Jane Bennett offers an even broader definition of life which includes inanimate entities as well. She stresses the inherent vitality of things and their ability to exhibit agency and uncanny power suggesting that they too should be perceived as subjects. Both theories argue against anthropocentrism and emphasize the interconnectedness and interdependence of human and non-human beings which give rise to a more profound awareness of the importance of environmental discourse.